2016
DOI: 10.1155/2016/6963582
|View full text |Cite
|
Sign up to set email alerts
|

ZFP91: A Noncanonical NF-κB Signaling Pathway Regulator with Oncogenic Properties Is Overexpressed in Prostate Cancer

Abstract: Novel molecular targets are being searched to aid in prostate cancer diagnosis and therapy. Recently, ZFP91 zinc finger protein has been found to be upregulated in prostate cancer cell lines. It is a potentially important oncogenic protein; however only limited data regarding its biological function and expression patterns are available. To date, ZFP91 has been shown to be a key factor in activation of noncanonical NF-κB signaling pathway as well as to be involved in HIF-1α signaling in cancer cells. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…Among studied cancer types only in the case of prostate cancer ZFP91 expression was significantly elevated in comparison to the unchanged prostatic tissue. Similarly as in our previous study on this subject (15), the increased (even 10-fold) ZFP91 mRNA quantity was present only in the fraction of cancer cases. ZFP91 overexpression on mRNA level was observed by Lee et al (3) in cancers of prostate, stomach and liver.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Among studied cancer types only in the case of prostate cancer ZFP91 expression was significantly elevated in comparison to the unchanged prostatic tissue. Similarly as in our previous study on this subject (15), the increased (even 10-fold) ZFP91 mRNA quantity was present only in the fraction of cancer cases. ZFP91 overexpression on mRNA level was observed by Lee et al (3) in cancers of prostate, stomach and liver.…”
Section: Discussionsupporting
confidence: 87%
“…Changes in ZFP91 mRNA levels observed in corresponding tissues were not reflected on a protein level. A discrepancy between mRNA and protein levels is often encountered (36)(37)(38)(39) and in the case of ZFP91 has been described in our previous works (14,15) as well as observed by the team of Lee et al (3). At this point of knowledge it seems that no clear correlation between ZFP91 mRNA and protein levels exist.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Numerous studies have reported that zinc finger protein 91 (ZFP91) promotes proliferation and tumorigenesis of different cancer types via regulation of the NF-κB p65 pathway (12)(13)(14). Therefore, to further investigate the regulatory mechanism of the miR-188-5p/ZFP91 axis, we detected the expression of NF-κBp65 and RelB in BC cells.…”
Section: Mir-188-5p/zfp91 Axis Regulates Nf-kb/p65 and Relb Expressionmentioning
confidence: 99%
“…Prostate cancer (PC) is the second most common cancer and the fifth leading cause of cancer deaths among men worldwide. A million new PC cases are diagnosed every year (Paschke et al, ). Historically, the incidence of PC has been lower in men from Asian countries than those from western countries (Lassed et al, ).…”
Section: Introductionmentioning
confidence: 99%